EFFECT OF ORGANIC MANURES, BIO-FERTILIZER AND MULCHING ON GROWTH AND YIELD OF POTATO (SOLANUM TUBEROSUM L.) - RAJESH KUMAR; AVTAR SINGH; VIKASH HOODA; R. K. SINGH; MAINPAL SINGH (The Bioscan, 2015)
An experiment on potato cv. Kufri Bahar was conducted at vegetable research farm, CCS Haryana Agricultural University, Hisar during 2010-11 and 2011-12. A set of sixteen treatment combinations were taken in sub plots while mulching and non-mulching in main plots under split plot design. All treatments showed superiority over control for plant height except biofertilizer treatment. Plant growth attributes like stem per hill, stem and leaves dry weight found significantly higher with the vermicompost + biofertilizer treatment followed by other treatments. Application of vermicompost 6.0 t/ha + Bio-fertilizer (Azotobacter + PSB) recorded maximum total yield (312 q/ha) and marketable yield (302 q/ha) followed by vermicompost treatment (311 q/ha) and (300 q/ha), respectively. It can be summarized that use of bio-fertilizer along with mulching proved useful in increasing growth and yield attributes and of potato crop significantly compared to control.